Visions of Volcanoes - David M. Pyle (19, 2017)
The long nineteenth century marked an important transition in the understanding of the nature of combustion and fire, and of volcanoes and the interior of the earth. It was also a period when dramatic eruptions of Vesuvius lit up the night skies of Naples, providing ample opportunities for travellers, natural philosophers, and early geologists to get up close to the glowing lavas of an active volcano. This article explores written and visual representations of volcanoes and volcanic activity during the period, with the particular perspective of writers from the non-volcanic regions of northern Europe. I explore how the language of ‘fire’ was used in both first-hand and fictionalized accounts of peoples’ interactions with volcanoes and experiences of volcanic phenomena, and see how the routine or implicit linkage of ‘fire’ with ‘combustion’ as an explanation for the deep forces at play within and beneath volcanoes slowly changed as the formal scientific study of volcanoes developed. I show how Vesuvius was used as a ‘model’ volcano in science and literature and how, later, following devastating eruptions in Indonesia and the Caribbean, volcanoes took on a new dimension as contemporary agents of death and destruction.